Accuracy of substance exposure history in patients attending emergency departments after substance misuse; a comparison with biological sample analysis. (2nd January 2023) - Virmani, Ishita; Oteo, Alberto; Dunn, Michael; Vidler, Daniel; Roper, Clair; Officer, Jane; Hardy, Gareth; Dargan, Paul I.; Eddleston, Michael; Cooper, Jamie G.; Hill, Simon L.; Macfarlane, Rebecca; et al.
Abstract: Context: Acute toxicity caused by illicit substance use is a common reason for emergency department (ED) presentation. Knowledge of the substances involved is helpful for predicting and managing potential toxicity, but limited information is available about the accuracy of patient-reported substance exposure. This study assessed the accuracy of the history of exposure in those reporting use of a single substance by comparison with those identified by detailed toxicological analysis, focusing on synthetic cannabinoid receptor agonists (SCRA). Methods: Adults (≥16 years) presenting between March 2015 and July 2021 to participating UK hospitals with toxicity after reporting use of a single illicit substance were included. Exposure details were documented from medical records and blood and/or urine samples analysed using high-resolution accurate mass liquid chromatography-mass spectrometry (HRAM LCMS). Sensitivity, specificity, and positive and negative predictive values of the exposure history were calculated by comparison with biological sample analysis ("gold standard"). Results: Single substance exposure was reported for 474 (median age 33 years, IQR: 18 range 16–75, 80% males) patients. Analysis commonly identified multiple substances (Median 3, IQR 2–5). A history of exposure was documented for 121 of 151 patients where a SCRA or metabolite was detected on analysis (sensitivity 80.1%, 95% CI 72.9, 86.2%). Corresponding proportions were lower for 3, 4-methylenedioxymethamphetamine (MDMA, 44/70, 62.9%., 95% CI 50.5%, 74.1%), heroin 41/108 (38.0% 95% CI 28.8–47.8%) and cocaine (22/56, 31.3%, 95% CI 20.9, 43.6%). Conclusions: Multiple undeclared substances were detected analytically in most patients reporting single substance use. Clinicians should be alert to the potential presence and toxicity of unreported substances when managing patients presenting after substance misuse.